Military intelligence and organized crime. Challenges to debate in Latin America - Sansó-Rubert, Daniel (FLACSO - Sede Ecuador, 2017)
The excessive growth of organized crime in Latin America, in terms of the plurality of manifestations and the seriousness of their impact, has led to a singular erosion of security, peaceful coexistence and social well-being, while at the same time breaching the consubstantial principles of democracy, violates fundamental rights and the criminal contagion of the economic and financial system. Faced with this situation of extreme gravity, many Latin American governments have resorted to the use of their Armed Forces to counteract the criminal threat. And these, within their novel attributions, have opted for the strategic use of intelligence capabilities in the fight against organized crime. Decision that has opened a relevant debate on the adequacy, not only of the recourse to the military establishment for this purpose - aside from the police forces -, but the delicate task of involving military personnel in intelligence work within the national territory with operational autonomy, detached from the respective national intelligence services, with all the prolegomena that such intervention can entail in operational terms and of democratic quality, and respect for the constitutional social and democratic state of law.